2015
DOI: 10.1111/neup.12220
|View full text |Cite
|
Sign up to set email alerts
|

Complex sarcolemmal invaginations mimicking myotendinous junctions in a case of Laing early‐onset distal myopathy

Abstract: Distal myopathies are a group of clinically and pathologically overlapping muscle diseases that are genetically complex and can represent a diagnostic challenge. Laing early-onset distal myopathy (MPD1) is a form of distal myopathy caused by mutations in the MYH7 gene, which encodes the beta myosin heavy chain protein expressed in type 1 skeletal muscle fibers and cardiac myocytes. Here, we present a case of genetically-confirmed MPD1 with a typical clinical presentation but distinctive light microscopic and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(36 reference statements)
4
3
0
Order By: Relevance
“…Muscle pathological changes in our patients including type 2 ber predominance, multi-cores and abnormal mitochondria, were relatively moderate and non-speci c, which were in accordance with previous researches [8,9,17,23]. Multi-cores were seen on muscle biopsy of patient II-2 (family D), and were also reported in some previous articles in patients with the same MYH7 mutation p.E1508del [16,24,25]. This could be a speci c pathological feature of this genotype.…”
Section: Discussionsupporting
confidence: 91%
“…Muscle pathological changes in our patients including type 2 ber predominance, multi-cores and abnormal mitochondria, were relatively moderate and non-speci c, which were in accordance with previous researches [8,9,17,23]. Multi-cores were seen on muscle biopsy of patient II-2 (family D), and were also reported in some previous articles in patients with the same MYH7 mutation p.E1508del [16,24,25]. This could be a speci c pathological feature of this genotype.…”
Section: Discussionsupporting
confidence: 91%
“…Muscle pathological changes in our patients including type 2 ber predominance, multi-cores and abnormal mitochondria, were relatively moderate and non-speci c, but were in accordance with previous researches [8,9,16,22]. Multi-cores on muscle biopsy of patient 6 were also reported in some previous articles in patients with the same MYH7 mutation p.E1508del [15,23,24]. This could be a speci c pathological feature of this genotype.…”
Section: Discussionsupporting
confidence: 91%
“…Referring to published articles on Laing distal myopathy, common mutation types also include missense mutations, and inframe indels. The p.K1617del and p.E1508del have also been reported in a few studies [5,6,8,9,12,15,19,23,24].Besides these in-frame indels in our study, other reported mutations include p.E1687del, p.K1729del, p.E1669del, p.K1729dup, p.L1793del, p.K1784del [5,9,11,16,[26][27][28]. Therefore, in-frame deletions or duplications are common types of mutations in Laing distal myopathy.…”
Section: Discussionsupporting
confidence: 83%
“…Muscle pathological changes in our patients including type 2 fiber predominance, multi-cores and abnormal mitochondria, were relatively moderate and non-specific, which were in accordance with previous researches [8,9,17,23]. Multi-cores were seen on muscle biopsy of patient II-2 (family D), and were also reported in some previous articles in patients with the same MYH7 mutation p.E1508del [16,24,25]. This could be a specific pathological feature of this genotype.…”
Section: Discussionsupporting
confidence: 91%